Variability in Asian parents’ English and mathematics skills: A family-based study - Pan, Dora Jue; Yang, Xiujie; Ku, Yuk Yee Serena; Dulay, Katrina May; Cheung, Sum Kwing; McBride, Catherine; Wong, Patrick Chun Man; Ho, Connie Suk Han (Frontiers in Education, 2022)
This study examined the factors explaining English and mathematics performances in Hong Kong and Philippines parents. Across both groups, parents who are younger or with higher education levels tended to perform better in English; parents’ literacy skills were uniquely associated with mathematics skills. In the Philippines only, mothers tended to be poorer in mathematics than fathers. Parents’ mathematics skills uniquely explained their English word reading. Moreover, children’s English skill also uniquely explained parents’ English performance. However, in Hong Kong only, family income was uniquely associated with parents’ English performance. Children’s mathematics performance was additionally associated with parents’ mathematics skills. Such results underscore the complex interactions among individual, family status, and intergenerational effects in explaining parents’ academic performances across cultures.